STUDY OF SURFACTANT FLOODING IN FIELD X USING NUMERICAL SIMULATION - BUNGSU KOMARUDIN (NIM : 22209085); Pembimbing : Ir. Taufan Marhaendrajana, M.Sc., Ph.D.; Ir. M, SETIA
Decreasing oil production of an oil field is a natural phenomenon, especially for brown field. Field X has been produce from 1961, in order to improve oil production; waterflood project has started at 1995 until now. However, after 15 years of waterflood project, it seems that waterflood become ineffective due to low oil production. Thus, surfactant flooding is proposed to improve waterflood efficiency. Surfactant injection has capability to decrease interfacial tension (IFT) of oil and water, thus mobilize trapped oil because of capillary force. Interaction between surfactant and reservoir properties is very complex and it will need a numerical simulation study for solving that complexity. A numerical simulation study is conducted to get better understanding of surfactant effect to oil production and black oil simulator (Eclipse E100 with activated surfactant option) is used in this study. The study is started by building of reservoir model, from data preparation to model calibration by history matching. After a representative reservoir model has been prepared, surfactant study is conducted for 15 years prediction. Various sensitivity studies are conducted, such as sensitivity study of surfactant concentration, duration of injection and injection technique. The most optimum scenario is scenario with 6 month interval slug 1% in 6 year time frame. Oil recovery factor increase about 9.2% (in 15 year) and net present value (NPV) is 28 million USD more than base case NPV.